TRENDS IN THE DIGITAL ECONOMY AND ITS DEVELOPMENT IN UZBEKISTAN - Tursunov Khasan Kholmuminovich (Scholar Express Journal, 2022)
The article analyzes the possibilities, advantages and disadvantages of the development of the digital economy in Uzbekistan, the level of development and describes the ways of further development of this sphere and elimination of existing shortcomings on the basis of the experience of developed countries
Keywords: Digital Economy, Development Trend; high efficiency; computer literacy